Pengaruh Fasilitas Belajar dan Motivasi Belajar Terhadap Prestasi Belajar Mahasiswa Jurusan Pendidikan Ekonomi 2017 Universitas Negeri Surabaya - Nuril Islamiyah (JPEKA: Jurnal Pendidikan Ekonomi, Manajemen dan Keuangan, 2019)
This study aims to determine the effect of learning facilities and learning motivation on the learning achievement of 2017 Economics Education Department students at Surabaya State University. This research includes the type of associative research with a quantitative approach. Respondents in this study were 172 students from the Economics Education Department, consisting of four study programs, namely PAK, PTN, PE, and PAP. The analysis test used is multiple linear regression test. The results showed that learning facilities and learning motivation had a positive and significant effect simultaneously on student learning achievement based on the statistical F test with a significant value of 0.00, meaning the sig <Î± (0.05) value, besides learning facilities had a positive and significant effect on achievement student learning partially with a significant value of 0.037 means the value of sig < Î± (0.05). Learning motivation also has a positive and significant effect on student learning achievement partially with a significant value of 0.00, meaning the value of sig <Î± (0.05) so that is rejected and is accepted. The coefficient of determination is based on the Adj R-Square table of 0.324.